Macroinvertebrate and microbial community responses to metal stress as measures of ecological recovery of a restored headwater stream - Wolff, Brian A., author; Clements, William H., advisor; Hall, Edward K., advisor; Kondratieff, Boris C., committee member; Schmidt, Travis S., committee member (Colorado State University. Libraries, 2020)
To view the abstract, please see the full text of the document.